THE MEDIATING EFFECT OF PRIVACY CONCERN ON INTENTION TO USE SELF SERVICE TECHNOLOGY IN HOTEL - Azlinda Hakim Binti Lokman Hakim; Hairunnisa Binti Mohamad Ibrahim (International Journal of Accounting, Finance and Business, 2023)
Self-service technology is an innovation that requires communication over the internet. In the hotel business, it has become more widespread as customers' interactions with service workers and technology have changed. Self-service technologies are increasingly valued by customers for their convenience, consistency, and control. Self-service technologies (SSTs) help hotels to improve service standards, and the wide range of technological applications available allows hotels to choose the application that best matches the needs of their guests as well as the hotel's needs. Despite their increasing popularity, some might have doubts about using the technology as this may involve confidentiality and privacy details. In the contact of Malaysian hotels, some have yet to fully integrate self-service technologies into their daily operations. The study proposes a research framework to suggest the direct and moderating roles of Privacy towards Intention to use SST. Extant research from various research streams is reviewed, resulting in 7 hypotheses. Data collected from customers with SST experiences are examined through PLS-SEM and hierarchical moderated regression analysis. Results indicate that customer privacy enhances perceived usefulness and perceived ease of use towards intention to use SST.